Need Analysis of the Development of Economics Interactive E-Module Based on Contextual Teaching and Learning for SMA - Lidia Aprileny Hutahaean; Siswandari Siswandari; Harini Harini (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study was aimed to conduct need analysis towards the development of interactive e-module based on Contextual Teaching and Learning (CTL) for the students of class X of SMA. This study was an initial research included in the development model of Four-D by Thiagarajan, et al. This study was limited at the define stage (need assessment) coming from the results of the observation, the interview, and the documentation. The define stage was conducted with: a) curriculum analysis, b) analysis of students’ characteristics, c) material analysis, and d) specifying instructional objectives. The data analysis was conducted descriptively and interpretatively. The subjects of the research were the economics teachers and the students of class X of SMA Negeri 6 Pematangsiantar. The result of the analysis showed that the curriculum used in SMA Negeri 6 Pematangsiantar was the 2013 curriculum in which the implementation emphasized on the use of the innovative learning media and strategy. From the characteristic of the cognitive development, the students of class X of SMA could study using Contextual Teaching and Learning. Besides, the students and the teachers were enthusiastic with the development of more interactive learning model. The material that was taught was the material of the Basic Concepts of Economicsby referring to the syllabus used by the school. The final objective that was achieved in this development research was to improve the economics learning outcomes of the students of SMA Negeri 6 Pematangsiantar. This study was the part of the development research of the interactive e-module based on CTL as the learning media of the students of class X of SMA to improve the economics learning outcomes of the students.